Pengaruh Penggunaan Media Audio Visual terhadap Hasil Belajar PAI Siswa SMP Sains Qur’an Pekanbaru - Nining Suniarti; Yenda Puspita (Kilau Publishing, 2026)
This study was motivated by the low interest of students in learning Islamic Religious Education due to the limited use of engaging learning media. The purpose of this study was to determine the effect of audio-visual media on students' interest in learning Islamic Religious Education at SMP Sains Qur'an Pekanbaru. This research employed a quantitative approach with a correlational research design. The population consisted of students of SMP Sains Qur'an Pekanbaru, while the sample comprised 27 students. Data were collected through observation, questionnaires, and documentation. The data were analyzed using descriptive analysis and the Chi-Square test to examine the research hypothesis. The findings revealed that the use of audio-visual media was categorized as good with a percentage of 63%, while students' interest in learning Islamic Religious Education was categorized as good with a percentage of 55%. The Chi-Square test result showed that the calculated value (χ² = 18.199) was higher than the critical values at both 5% and 1% significance levels, indicating that the alternative hypothesis was accepted. Therefore, there was a significant effect of audio-visual media on students' interest in learning Islamic Religious Education at SMP Sains Qur'an Pekanbaru. Based on these findings, teachers are recommended to optimize the use of audio-visual media to enhance students' learning interest and create more engaging and effective learning activities.